MENYINGKAP SISI KEMUKJIZATAN AL-QUR’AN - Muhammad Amin (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2017)
Extraordinary events that surpass the ability of the human senses to understand it in Islamic literature are called miracles. Miracles become one of the signs of the truth of a prophet sent by Allah SWT. The Qur'an is the greatest miracle given to the last prophet, the Prophet Muhammad. By the scholars of the Koran there have been various studies on the extraordinary aspects contained in the Koran. They found many amazing things in it. So as to provoke other researchers to uncover and reveal other extraordinary sides contained in it. This brief article narrates some of the extraordinary aspects contained in the Qur'an that have been studied by experts in their fields